PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SMALL GROUP WORK - Andari Duhita Jayanti; AA Sujadi (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research was to improve the learning motivation and learning achievement in mathematic of student of class VIIC SMP N 22 Purworejo using learning type Small Group Work. The subjects of this research were student of class VIIC SMP N 22 Purworejo totaling 31 students. The object of this research was learning motivation and mathematic learning achievement. The result showed that after application of using learning type Small Group Work in class VIIC SMP N 22 Purworejo, learning motivation and mathematic learning achievement of student has increased. This was indicated by an increase in the result percentage average learning motivation score of 39,78% in the pre-action, whereas at the first cycle improves with average percentage 55,61%. In the second cycle improve to 78,01%. Mathematic learning achievement of student also increased. At the beginning of the test the ability is 64,32. In the first cycle, the average result improves to 76,26. In the second cycle the average result improves to 85,30.